2021
DOI: 10.1021/acsami.1c08581
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Activation of Diazirine Biomaterials with the Blue Light Photocatalyst

Abstract: Carbene-based macromolecules are an emerging new stimuli-sensitive class of biomaterials that avoid the impediments of free radical polymerization but maintain a rapid liquid-to-biorubber transition. Activation of diazirine-grafted polycaprolactone polyol (CaproGlu) is limited to UVA wavelengths that have tissue exposure constraints and limited light intensities. For the first time, UVA is circumvented with visible light-emitting diodes at 445 nm (blue) to rapidly activate diazirine-to-carbene covalent cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…We and others have shown that diazirine-based reagents can be useful for cross-linking and/or functionalizing low-functionality commodity polymers, including polyethylene (Figure A). The diazirine group can be activated thermally (by treatment with temperatures above 100 °C) or photochemically (by excitation with 350–365 nm light), , or else through the application of an electric potential (−1.6 V vs Ag/AgCl) or through the use of a photosensitizer. , In all cases, high-energy carbenes are produced, which engage in promiscuous C–H insertion reactions along the aliphatic backbone of the polymer. This process, which results in the installation of strong covalent linkages to the polymer surface, can be harnessed to irreversibly link dyes and photosensitizers to polymers and can also be exploited in fabric strengthening and adhesion applications…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that diazirine-based reagents can be useful for cross-linking and/or functionalizing low-functionality commodity polymers, including polyethylene (Figure A). The diazirine group can be activated thermally (by treatment with temperatures above 100 °C) or photochemically (by excitation with 350–365 nm light), , or else through the application of an electric potential (−1.6 V vs Ag/AgCl) or through the use of a photosensitizer. , In all cases, high-energy carbenes are produced, which engage in promiscuous C–H insertion reactions along the aliphatic backbone of the polymer. This process, which results in the installation of strong covalent linkages to the polymer surface, can be harnessed to irreversibly link dyes and photosensitizers to polymers and can also be exploited in fabric strengthening and adhesion applications…”
Section: Introductionmentioning
confidence: 99%
“…Bis-diazirines have been reported to act as crosslinkers for low surface energy plastics and have also been used for crosslinking of solution processed organic LEDs . Furthermore, our recent study demonstrated activation of CaproGlu can be expanded to visible light activation with the aid of photocatalysts . Unlike UV activation, visible light does not produce diazoalkane.…”
Section: Discussionmentioning
confidence: 95%
“…Hybrid polymer composites would expand the adhesive’s rheological properties with respect to the precured state (e.g., apparent viscosity) and post-cured (e.g., shear strength). Liquid, hydrophobic carbene-based bioadhesives are currently modeled on diazirine-grafted polycaprolactone polyols (referred to as CaproGlu). Thus, CaproGlu’s rheological properties may be expanded through simple mixing of liquid polymer additives, but the competing effect of nucleophilic functional groups on carbene insertion remains unknown. CaproGlu comprised a four-arm polycaprolactone oligomer where two chains are grafted with TPDs and the remaining two with hydroxyl end groups, as shown in Figure . , …”
Section: Introductionmentioning
confidence: 99%
“…The effect of light penetration on mechanical properties of the composites could be further studied following recent findings of visible light activation of diazirine. 62 Lyophilized composite formulations are found to loose part of their material properties upon rehydration (6–9 times reduction in G ′ max, 2–3 times higher gelation dose, 6–10 times reduction in yield stress, Fig. S9, ESI†).…”
Section: Discussionmentioning
confidence: 99%